Processing Sequential Sensor Data - Krumm, John (Ubiquitous Computing Fundamentals, 2010)
This book is an overview of the fascinating field of ubiquitous computing. Since this field is rapidly progressing, the book is aimed at people who want to explore it as researchers or track its evolution. Intended for advanced undergraduates, graduate students, and professionals interested in ubiquitous computing research, the book covers the major fundamentals and research in the key areas that shape the field. Each chapter is a tutorial that provides readers with an introduction to an important subset of ubiquitous computing and also contains many valuable references to relevant research papers. The field of ubiquitous computing is simultaneously young and broad. Research papers in the field commonly reference Mark Weiser, who famously coined the term “ubiquitous computing” in his Scientific American article in 1991. This is considered the start of the research area, and it has grown to encompass a broad array of technologies since then. While the field is broad, there are well-established conferences and researchers devoted to it. We chose eleven of the most prominent ubiquitous computing research devotees to contribute chapters to this book in their area of expertise. Given the field’s breadth, it would be difficult to find one person who can expertly cover it all. Some of the chapter authors teach ubiquitous computing at universities. All of them are intimately involved in research in their specialty. Working in the area means they have the experience to not only describe the fundamental research issues, but to also explain practical ways to accomplish research and publish papers in the field.